The Legacy of Althusser, 1918-1990: An Introduction - Philip Goldstein (Studies in 20th & 21st Century Literature, 1994)
Introduction to the special issue.
Keywords: scientific; rationalist features; Althusser; post-structuralist aspects; post-structuralism; Foucauldian; discourse; power; Pour Marx; normative; science; ideology; ideological history; formal; scientific ideals; totalizing approaches; Foucault; archaeological studies; Tony Bennett; Foucauldian critique; traditional aesthetic; Marxist aesthetic